Antenatal detection of chromosomal abnormalities combining QF-PCR and cytogenetic analysis - Vičić, Ana; Škaro, Vedrana; Projić, Petar; Korać, Petra; Gjergja Juraški, Romana; Stipoljev, Feodora (2020)
Aim: To compare the diagnostic values and limitations of quantitative fluorescent polymerase chain reaction (QF-PCR) and conventional cytogenetic analysis in prenatal diagnosis of chromosomal abnormalities. Methods: A prospective study included simultaneous QF-PCR and cytogenetic analysis of 133 prenatal samples routinely obtained by amniocentesis or chorionic villus sampling (CVS). Additionally, QF-PCR analysis was performed on 14 tissue samples collected after termination of pregnancy (TOP) for which karyotyping could not be performed due to culture failure. Results: Among 133 analyzed prenatal samples, chromosomal abnormalities were diagnosed in 12 cases (9%), including 10 cases of numerical chromosomal aberrations and two cases with unbalanced structural rearrangements. Nine out of 12 chromosomal abnormalities were also detected with QF-PCR. However, all cases of major aneuploidies were successfully disclosed with QF-PCR, resulting in 100% detection rate for chromosomes 21, 18, 13, X and Y. Using a set of markers specific for chromosomes 21, 18 and 13, QF-PCR analysis of tissues collected after TOP revealed chromosomopathy in 21.4% of cases (two cases of trisomy 18 and one triploidy). A comparison of STR markers confirmed monozygosity in two monochorionic/diamniotic twin pregnancies. Conclusion: QF-PCR has been shown as a rapid and reliable method for prenatal diagnosis of the most common chromosomal aneuploidies, and as an adequate alternative to conventional karyotyping in cases where cytogenetic analysis is not possible due to failure of culturing process. However, conventional cytogenetics still presents a gold standard for the detection of structural aberrations and rare aneuploidies.
Bibliografija: 36 jed.
Abstract.
Keywords: Kromosomska abnormalnost -- Citogenetska analiza -- Prenatalna dijagnostika -- Pobačaj